MENINGKATKAN MUTU PENDIDIKAN MENGGUNAKAN GAYA KEPEMIMPINAN VISIONER - M. Aditya Salam; Naila Putri Imani; Muhammad Sirozi (LP2M IAIN Sultan Amai Gorontalo, 2026)
Improving the quality of education is one of the main challenges faced by educational institutions in the era of globalization and the Industrial Revolution 4.0. In this context, visionary leadership serves as a strategic key to guiding all school components toward achieving a future-oriented educational vision and goals. This study aims to analyze the role and implementation of visionary leadership styles in improving the quality of education in schools. The focus of this research is on how school principals, as visionary leaders, are able to integrate vision, collaboration, innovation, and transformative values into their leadership practices. This study employs a qualitative method with a case study approach, in which data were collected through in-depth interviews, participatory observations, and documentation analysis of the principal’s leadership activities and managerial dynamics within the school environment. The results reveal that visionary leadership plays a significant role in building an adaptive organizational culture, enhancing teacher performance through motivation and empowerment, and creating a conducive and quality-oriented learning environment. Furthermore, the visionary leadership style has proven effective in optimizing human resources, facilitating collaboration among stakeholders, and encouraging educational innovation. Therefore, the implementation of visionary leadership can serve as an effective model for achieving sustainable improvement in educational quality.